A simple and robust approach to reducing contact resistance in organic transistors. Issue 1 (December 2018) - Lamport, Zachary; Barth, Katrina; Lee, Hyunsu; Gann, Eliot; Engmann, Sebastian; Chen, Hu; Guthold, Martin; McCulloch, Iain; Anthony, John; Richter, Lee; DeLongchamp, Dean; Jurchescu, Oana
Abstract Efficient injection of charge carriers from the contacts into the semiconductor layer is crucial for achieving high-performance organic devices. The potential drop necessary to accomplish this process yields a resistance associated with the contacts, namely the contact resistance. A large contact resistance can limit the operation of devices and even lead to inaccuracies in the extraction of the device parameters. Here, we demonstrate a simple and efficient strategy for reducing the contact resistance in organic thin-film transistors by more than an order of magnitude by creating high work function domains at the surface of the injecting electrodes to promote channels of enhanced injection. We find that the method is effective for both organic small molecule and polymer semiconductors, where we achieved a contact resistance as low as 200 Ωcm and device charge carrier mobilities as high as 20 cm2 V−1 s−1, independent of the applied gate voltage. Minimizing contact effects in organic semiconductor-based devices is a key step toward the development of a low-cost technology for next-generation electronics. Here, the authors reduce contact resistance in organic devices by engineering electrodes with high work function surface domains.